The Right to Explanation in Artificial Intelligence–Based Decision-Making: A Normative Perspective on Due Process and Legal Accountability - Imroatun Solekah; Sahal Hanafi; Wildan Baehaqi; Teddy Delano (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The increasing adoption of artificial intelligence (AI) in legally significant decision-making has generated fundamental challenges concerning procedural fairness, transparency, and legal accountability. This article examines the juridical status of the right to explanation in AI-based decision-making through a normative and doctrinal legal research approach supported by comparative analysis of contemporary regulatory frameworks and legal theories. The study analyzes international legal instruments, administrative law principles, data protection regulations, accountability doctrines, and scholarly debates addressing explainability, due process, and algorithmic governance. The findings demonstrate that explanation performs a constitutive legal function within procedural justice by enabling meaningful participation, contestation, review, and accountability. Existing legal frameworks increasingly recognize the necessity of explainability, although regulatory approaches remain fragmented regarding its normative scope and enforceability. The analysis further reveals that accountability for AI-generated decisions must remain attached to identifiable human and institutional actors, regardless of technological complexity. Recognition of the right to explanation as an enforceable procedural guarantee strengthens legality, safeguards individual rights, and preserves rule-of-law values within automated governance systems. The study contributes a coherent normative framework connecting explainability, due process, and legal accountability in contemporary AI regulation.